2021
DOI: 10.1039/d1ta03610f
|View full text |Cite
|
Sign up to set email alerts
|

Innovative salt-blocking technologies of photothermal materials in solar-driven interfacial desalination

Abstract: In recent decades, a rapid development of solar water evaporation has been ushered, which focus on low-cost and energy water desalination. For this purpose, different photothermal materials have been introduced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 119 publications
0
61
0
Order By: Relevance
“…Based on the results mentioned above, as a pure organic molecule TPA‐TPA‐O 6 is a very stable and high‐performance photothermal conversion material with an extremely wide and rarely reported absorption spectra in our test condition including powder and dispersed state in polyurethane (PU) (Figure 6C) [23] . Its unique absorption characteristics make it promising to capture solar energy in solar‐driven water evaporation [24] . We employed a commercially available white PU porous foam as support to establish an efficient interfacial evaporation system by floating on water (Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results mentioned above, as a pure organic molecule TPA‐TPA‐O 6 is a very stable and high‐performance photothermal conversion material with an extremely wide and rarely reported absorption spectra in our test condition including powder and dispersed state in polyurethane (PU) (Figure 6C) [23] . Its unique absorption characteristics make it promising to capture solar energy in solar‐driven water evaporation [24] . We employed a commercially available white PU porous foam as support to establish an efficient interfacial evaporation system by floating on water (Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
“…[23] Its unique absorption characteristics make it promising to capture solar energy in solar-driven water evaporation. [24] We employed a commercially available white PU porous foam as support to establish an efficient interfacial evaporation system by floating on water (Figure 6D). TPA-TPA-O 6 was loaded inside the PU foam by impregnating pure PU foam in solution and drying under 80 °C, obtaining a brownish black PU foam (Figure S20).…”
Section: Methodsmentioning
confidence: 99%
“…Solar driven evaporation devices still suffer the issues of low salt resistance and poor stability. Pioneer work indicated that the porous surface and water pathway can efficiently decrease the salt aggregation during the evaporation process [20][21][22]. In this research, a highly efficient and anti-salt solar evaporator based on composites of laser induced graphene (LIG) and Cu plasmonic has been facilely developed.…”
Section: Introductionmentioning
confidence: 99%
“…This salt fouling issue becomes more concerning when the solar evaporators are operated with a high salinity of seawater. Although progressive strategies such as constructing hydrophobic surfaces , or designing interconnected convective porous channels , have exhibited some accessibilities to avoid salt accumulation, it is hard to achieve a high evaporation rate while simultaneously maintaining long-time operation continuity because of the heat loss. Moreover, in most solar evaporators, the photothermal materials are generally deposited onto fragile substrates with limited mechanical strength [e.g., anodic aluminum oxide membranes, cellulose paper, nanofiber membranes, aerogels, , or rigid substrates with poor flexibility (e.g., wood, , metallic foam)], which makes them not durable and hard to clean once contaminated or fouled during practical applications. Also, the current prototypes of evaporators are still restrained to complicated preparation procedures, limited sizes, poor washability and scalability, etc.…”
Section: Introductionmentioning
confidence: 99%